O aparato jurídico institucional como mecanismo propulsor da “biomercadoria” transgênica em detrimento dos direitos à conservação da biodiversidade e à soberania alimentar: uma análise dos riscos socioambientais. - Carnaúba, Tatianna Gomes Voronkoff (2015)
This study aims at the checking of effectiveness of international and national legal and institutional frameworks for the control of environmental and socioeconomic risks resulting from the use of genetically modified organisms before the largest commitment to guarantee the right to an ecologically balanced environment and the right to food sovereignty. This issue is relevant because of the serious environmental and socioeconomic threats that may result from implementation of such risks, considering the hypothesis that they were not studied and controlled by a rigorous precautionary approach. In order to achieve this goal, both bibliographic and documentary research were required. The bibliographic research allowed a better comprehension of the Theory of Risk Society and of the social and environmental risks associated with genetically modified crops. This bibliographic research also supports the analysis of international and national legal system, the judicial control of administrative discretion and the historic of the release of transgenic soybeans in Brazil. The basis of the documentary research are the Brazilian judgments dedicated to the release/ban of genetically modified organisms in the country and a specific contract for the commercial exploitation of transgenic soybeans. A number of relevant problems, arising from risk control exercised by administrative, legislative, judicial and contractual means, was duly identified. Based on this study, it was concluded the urgent need to reform these legal instruments, given their inability in achieving adequate precaution procedures so that these risks are effectively understood and controlled.